Review of David Campbell, Contractual Relations – A Contribution to the Critique of the Classical Law of Contracts (Universidad de San Andres Law Review, 2025)
Review of DDavid Campbell, Contractual Relations: A Contribution to the Critique of the Classical Law of Contracts (Oxford: Oxford University Press, 2022).